Analisis Deiksis Semantik Dalam Cerpen Bawang Putih Bawang Merah - Siagian, Irwan; Shofyan, Muhammad Shofiyudin; Abadi, Muhammad Adilah; Lutfiyanti, Nur Anisa; Prayono, Novi Monicka; Mufidah, Ana; Stevany, Marlina; Nurhadijah, Nabila (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The aims of this research are: (1) To describe the types of persona deixis found in the short story collection